Bullying di Sekolah Dasar: Faktor Penyebab, Dampak, dan Langkah Antisipasi - Akhmad Syah Roni Amanullah; Azhar Md Adnan (Program Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2025)
Bullying in elementary schools remains a critical concern as it hampers students’ socio-emotional development, academic progress, and mental well-being. This study aims to analyze the contributing factors, forms of bullying behavior, its impacts, and the preventive measures that can be implemented in elementary school settings. Employing a quantitative descriptive approach, data were collected using questionnaires administered to elementary school students. The data were analyzed using frequency distributions and percentage tabulations to identify patterns of bullying behavior and its underlying causes. The findings reveal that the most dominant factors include imbalanced social interactions, peer-group influences, and inadequate teacher supervision. The impacts experienced by students involve decreased learning motivation, emotional disturbances such as anxiety and social withdrawal, as well as the potential emergence of further aggressive behaviors. Effective preventive measures include the implementation of empathy-based character education, strengthening teachers’ supervisory roles, fostering a safe and inclusive school culture, and enhancing parental involvement in school communication. This study emphasizes the importance of collaborative efforts among all school stakeholders to create a bullying-free learning environment and to support students’ holistic development.